2016
DOI: 10.1016/j.atherosclerosis.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of vascular smooth muscle cells is induced by secondary calciprotein particles and enhanced by tumor necrosis factor-α

Abstract: Secondary, but not primary CPP, induce VSMC calcification. Secondary CPP induce the expression and release of TNF-α, which enhances calcification via its receptor TNFR1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
185
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(226 citation statements)
references
References 48 publications
(64 reference statements)
7
185
1
11
Order By: Relevance
“…Inflammatory cytokines such as TNF-α may induce exosome secretion from VSMCs and thereby increase the procalcific properties of serum [57, 58]. Therefore, reducing the levels of pro-inflammatory molecules may limit the progression of vascular calcification [54-56, 59, 60]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cytokines such as TNF-α may induce exosome secretion from VSMCs and thereby increase the procalcific properties of serum [57, 58]. Therefore, reducing the levels of pro-inflammatory molecules may limit the progression of vascular calcification [54-56, 59, 60]. …”
Section: Discussionmentioning
confidence: 99%
“…IL-6 [52, 53], TNF-α [54-56] and VCAM [22] have been discussed as key inducers of vascular calcification. Hence, reducing these molecules may provide a possible explanation for the observed effects on VSMC calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Primary CPP is considered to inhibit crystal growth and aggregation [44], but it undergo spontaneous maturation and develop crystalline structures to form secondary CPP. Aghagolzadeh et al have recently reported that secondary CPP has a potential to induce vascular calcification [45]. In addition, CPP maturation time (T 50 ) has been reported as an independent predictor of mortality in HD patients [46] and renal transplant recipients [47].…”
Section: Mg and Dialysis Therapymentioning
confidence: 99%
“…Vascular calcification in patients with CKD occurs via osteoblastic-like cell differentiation of the vascular smooth muscle cells in the kidneys. Some studies reported that cyclic adenosine monophosphate, which is mediated by tumor necrosis factor-α, stimulates the osteoblastic differentiation of vascular smooth muscle cells in kidney [36, 37]. In other studies, high extracellular calcium and phosphate concentrations have induced the transformation of vascular smooth muscle cells into osteoblast-like cells and accelerated the processes of active vascular calcification [38, 39].…”
Section: Discussionmentioning
confidence: 99%